A review of nanofluid stability properties and characterization in stationary conditions - Ghadimi, A.; Saidur, Rahman; Metselaar, H.S.C. (Elsevier, 2011)
A new engineering medium, called nanofluid attracted a wide range of researches on many cooling processes in engineering applications, which are prepared by dispersing nanoparticles or nanotubes in a host fluid. In this paper, the stability of nanofluids is discussed as it has a major role in heat transfer enhancement for further possible applications. It also represents general stabilization methods as well as various types of instruments for stability inspection. Characterization, analytical models and measurement techniques of nanofluids after preparation by a single step or two-step method are studied.